The Survey Work of the Danish Geodetic Institute in Greenland and Iceland - Nørlund, N. E. (Polar Record, 1939)
This work was commenced in 1927 and has been continued ever since without interruption. Every spring the Institute has sent an expedition to Greenland with the ordinary line steamers. In Greenland, transport to the working places proceeds by means of four fast motor-boats specially built for this work. They are very suitable for use in the numerous rocky fjords and sufficiently large to traverse the long distances from one end of the field of operations to the other. The frequent transfer of the surveyors from one station to another is not the least of the difficulties which the organisation of the survey work in Greenland presents. The distance run by a survey boat during a summer has often exceeded 3500 nautical miles and even reached 5600 miles. There are wireless transmitters and receivers on each boat in order to maintain communication between the different survey parties. Besides the four larger boats, the survey has the use of ten smaller boats for sailing in sheltered waters.